Pointwise estimate of a solution to quasilinear elliptic problem in the domain with thin cavity - Skrypnik, I. V.; Naumova, M. A. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
We derive a pointwise estimate of the solution to Dirichlet’s problem for a quasilinear second–order elliptic equation in a domain whose bounded compliment is contained in a small neighborhood of a set $\{x\in R^n: |x|≤ ½,x_1=…=x_s=0\}$.